Dance and Motion as a Means Of Expression in the New Circus Analysis of the Performance „Dralion” by Cirque du Soleil (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
The article is an analysis of the performance entitled Dralion by Cirque du Soleil. The author locates the circus shows in the context of other performing arts, especially dance and dance theatre, using among others the theories of Richard Schechner and Erving Goffman. Special attention is paid to the performer’s body concerning the works of the following dance researchers: Sondra Horton Fraleigh, Ewa Wycichowska and Dominika Byczkowska. The body is the main instrument, both for the circus artists and for actors or dancers. In all of these arts it is the body that conveys meanings, emotions and reflections. In case of the circus, the body is also the topic itself – the viewers admire its agility and fitness. The work of the circus ‘body masters’ (according to Alessandro Serena’s classification) is based on overcoming its weaknesses and limits, on achieving what seems to be unachievable. However, the New Circus, represented by the Canadian group, uses performer’s body as a means of expression in the way which is close to dance and theatre. Dance is also a way of meanings’ communication – through using and even parodying some traditions and conventions. The performance Dralion is, therefore, situated somewhere on the boundary of the circus and dance theatre. The New Circus, combining the elements of the traditional circus, dance theatre and other arts, can be analysed in the context of contemporary tendencies for arts synthesis and aesthetics of stimulation described by Jean-Marie Pradier.